Representasi Maskulinitas Toksik pada Tokoh Utama dalam Film "Seperti Dendam, Rindu Harus Dibayar Tuntas" - Vanie, Adevy; Meviana, Marthalinda (Jurnal Mahardika Adiwidia, 2022)
Toxic masculinity is interpreted from the character of masculinity in general but is carried out in a very excessive manner so as to harm others around him, as in this film which reflects the life of the male main character who always puts his emotions first and commits violence. John Fiske's semiotic analysis method with a qualitative approach through three levels of coding, namely the level of reality that can be judged from the environment and behavior, the level of representation that can be seen from the setting as well as the camera angle, and the level of ideology that can be judged from reality and representations that are described as ideological codes. The result of writing is that there are verbal and non-verbal signs such as facial expressions, gestures, conversations of the main character. The main character also seems to always prioritize emotion and violence in every problem solving, the opponent dominates the conversation, is more aggressive, rude, and wants to look macho to cover his shortcomings, which is a sign of the bad influence of masculinity domination that is forced, misunderstood and abused. As well as the ideology of individualism that does not care about its surroundings.